Endothelial progenitor cells: a new player in lupus? - Haque, Sahena (BioMed Central, 2012)
Patients with systemic lupus erythematosus (SLE) have a greatly increased risk of cardiovascular disease. There is growing interest in the link between vascular damage and lupus-specific inflammatory factors. Impaired endothelial repair could account for the endothelial dysfunction in this patient group. This review describes the contribution that endothelial progenitor cells could play in the pathogenesis of premature vascular damage in this disease. The methods of isolation, detection, and characterization of endothelial progenitor cells, together with their potential role in repair of the endothelium and as a therapeutic target in SLE, are discussed.